The Effectiveness of Know-Want-Learn (KWL) Technique to Improve Students’ Reading Comprehension - Serly Marliasari; Eka Haryati Yuliany; Yuliani, Sri; Saraswaty, Dwi Rara (Holistics (Hospitality and Linguistics) : Jurnal Ilmiah Bahasa Inggris, 2024)
ABSTRACT: The purpose of this research was to find out whether or not it was effective to use Know-Want-Learn (KWL) technique to improve students’ reading comprehension at the Fifth Semester Students of English Education Study Program Universitas Muhammadiyah Palembang. This research was done through Quasi-experimental method including technique for collecting the data and technique for analyzing the data. The population numbers was 36 students, and used the convenience non random sampling. Based on statistic analysis of independent sample t-test, the result of students’ score in experimental group and control groups that the value of t-obtained 5.224 was higher than t-test (1.671). It could be concluded that Ho (Null Hypothesis) was rejected and Ha (Alternative Hypothesis) was accepted. The result of the students’ reading comprehension in the posttest of experimental group was (85.30) which were higher than control group which was not through (KWL) with (76.38) as the highest score. It means that the use of this KWL is significance. Keywords: Teaching, Known-Want-Learn (KWL), Reading Comprehension